2018
DOI: 10.1016/j.actatropica.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of human cystic echinococcosis in Basrah province, Iraq

Abstract: Human cystic echinococcosis (CE) is a parasitic zoonosis with serious clinical burden and constitutes a challenge to public health in endemic areas worldwide. We performed a retrospective study to investigate the occurrence of CE in patients at six hospitals in Basrah province, Iraq. In the current study setting, data retrieval and validation of the quality of hospital records was very challenging considering the difficult situation Iraq is unfortunately facing. Hospitalization records were reviewed from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
15
24
0
Order By: Relevance
“…In the current analysis, gender distribution of CE was studied based on hospitalization records and it revealed that females (58.5%) acquired more disease than males. Similar findings were reported in Iraq [ 27 ] and Iran [ 16 ]. The probable reason for this can be increased interaction to potential risk factors including livestock management and poor living hygenic conditions.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In the current analysis, gender distribution of CE was studied based on hospitalization records and it revealed that females (58.5%) acquired more disease than males. Similar findings were reported in Iraq [ 27 ] and Iran [ 16 ]. The probable reason for this can be increased interaction to potential risk factors including livestock management and poor living hygenic conditions.…”
supporting
confidence: 91%
“…In the present study age distribution showed that the highest number of infected individuals lied in 21–30 years. Similar retrospective studies in Iraq showed high rate same higher rate of infection among 21 to 30 years age group [ 27 ]. the mean affected age in current study was 35+−17.…”
supporting
confidence: 53%
“…In the current study, women were found to be at higher risk of CE infection than men. This finding is in line with our previous study and also a study by Abdulhameed in Iraq, where females were reported to be the main victim of CE, in a retrospective hospital-based study conducted in a neighboring city, Basrah in Iraq [5,13]. Previous studies suggested that women have the highest chance of contact with sources of infection such as dogs, soil, vegetable, etc.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence rate of CE in Iran has been reported to be 1.3-3/100,000 population. A higher rate of incidence (4.5 cases/100,000 /year) has been reported in neighboring Iraq [13].…”
Section: Discussionmentioning
confidence: 76%
“…Official written approval to review hospital records and to contact patients was obtained from the Ministry of Health in Iraq and from the Basrah Health Directorate. Of six hospitals in Basrah from which previous incidence data had been collected [15], four gave permission to interview hospitalised patients with CE after surgical intervention, or to contact patients who had undergone surgery between 2014 and 2016. The hospitals were visited four times a week from May to July 2016, and 19 current patients were recruited.…”
Section: Case Recruitment and Questionnaire Administrationmentioning
confidence: 99%